ANALISIS KEBIJAKAN HEDGING DALAM MENGELOLA RISIKO PEMBIAYAAN PADA BANK SYARIAH DI INDONESIA - jurnal khitabah; Acim Acim (KHITABAH: Khazanah Penelitian Perbankan Syariah, 2024)
This study aims to analyze the hedging policy in managing financing risks in Islamic banks in Indonesia. Given the crucial role of Islamic banks in the economy, efficient financing risk management is key to maintaining financial stability. The hedging policy implemented by Islamic banks can help mitigate risks arising from market fluctuations, credit risks, and operational risks. This research uses a quantitative approach with regression analysis to measure the impact of hedging instruments on non-performing financing (NPF) in Indonesian Islamic banks. The data includes annual reports from several Islamic banks registered with the Financial Services Authority (OJK) from 2018-2022. The results show that the hedging policy significantly reduces NPF. Hedging instruments such as wa'ad, tawarruq, and kafala were found to be effective in reducing market risk exposure and improving the quality of financing. However, the findings also reveal that smaller Islamic banks tend to face challenges in implementing complex hedging policies due to cost constraints and limited knowledge. This study recommends that smaller Islamic banks be provided with training and support to implement hedging policies more effectively, as well as the importance of developing simpler and more affordable hedging instruments